1993
DOI: 10.2165/00002512-199303060-00005
|View full text |Cite
|
Sign up to set email alerts
|

Problems and Pitfalls of Sulphonylurea Therapy in Older Patients

Abstract: The prevalence of non-insulin-dependent diabetes mellitus (type II) increases with age, so that approximately half of all known patients in English-speaking countries are over 65 years of age. There is no reason to believe that the criteria for blood glucose control should be any less stringent for elderly patients unless they have a limited life expectancy. Sulphonylurea drugs remain an effective means of achieving blood glucose control after failure of dietary therapy alone in older patients. However, change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…They are most likely to be effective in patients whose weight is in the normal range [80]. Hypoglycaemia is the most troublesome effect and is more common with second-generation SUs, which have longer half-lives [87]. SU drugs such as tolazamide, acetohexamide, chlorpropamide and glibenclamide (glyburide) are more likely to cause signifi cant hypoglycaemia, as the metabolism of these drugs, compared with other commonly prescribed SUs, can lead to the accumulation of either the parent drug or the active metabolite in the presence of renal insuffi ciency.…”
Section: Mechanism Of Action Of Oral Hypoglycaemic Drugsmentioning
confidence: 99%
“…They are most likely to be effective in patients whose weight is in the normal range [80]. Hypoglycaemia is the most troublesome effect and is more common with second-generation SUs, which have longer half-lives [87]. SU drugs such as tolazamide, acetohexamide, chlorpropamide and glibenclamide (glyburide) are more likely to cause signifi cant hypoglycaemia, as the metabolism of these drugs, compared with other commonly prescribed SUs, can lead to the accumulation of either the parent drug or the active metabolite in the presence of renal insuffi ciency.…”
Section: Mechanism Of Action Of Oral Hypoglycaemic Drugsmentioning
confidence: 99%
“…This risk will also be compounded when sulphonylureas that are renally excreted (or that have renally-excreted active metabolites) are used in patients with compromised renal function. 45 Food intake may also adversely affect the temporal pro®le of stimulated insulin secretion during sulphonylurea therapy. Single dose studies have shown 2.5 mg of glibenclamide taken 30 min before breakfast to be more effective than 7.5 mg taken with breakfast, 46 while concomitant food intake has been shown to delay the absorption of glipizide.…”
Section: Conventional Hypoglycaemic Agents: Kinetic Limitationsmentioning
confidence: 99%
“…The prolonged action of these drugs means that stimulation of insulin release extends well beyond mealtimes, and may therefore be inappropriately high when glucose levels are not elevated. Under these circumstances, hypoglycemia is an ever-present risk, and the patient treated with a SU must ensure an adequate carbohydrate intake throughout the day to counter this threat; a missed meal is particularly likely to result in a hypoglycemic episode (35,36). Indeed, symptomatic hypoglycemia is the most common side effect associated with SU therapy, particularly in elderly patients, and irregular meals have been identified as a contributing factor in this high incidence (35).…”
Section: Insulin Secretagogues Hypoglycemia and Mealtime Flexibilitymentioning
confidence: 99%
“…Under these circumstances, hypoglycemia is an ever-present risk, and the patient treated with a SU must ensure an adequate carbohydrate intake throughout the day to counter this threat; a missed meal is particularly likely to result in a hypoglycemic episode (35,36). Indeed, symptomatic hypoglycemia is the most common side effect associated with SU therapy, particularly in elderly patients, and irregular meals have been identified as a contributing factor in this high incidence (35). Accumulation of SUs that are partially excreted by the renal route may be another reason for an increased risk of hypoglycemia in elderly patients (35).…”
Section: Insulin Secretagogues Hypoglycemia and Mealtime Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation